Diversifikasi Kurikulum Pendididikan Tinggi Islam - Diyana Rizky, Febri; Ahmadi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Every Islamic university has the same ideals in order to provide effective, efficient and quality educational services, one of which can be achieved by diversifying the curriculum. The purpose of this study is to examine the diversification of the curriculum in Islamic higher education at Al-Amien Prenduan University. This study is a field research with a qualitative approach, while the type of research in this study is a case study, which is located at Al-Amien Prenduan University, Sumenep. The primary sources in this study include Fathorrahman, Ach. Nurholis Majid, Heri Fadli Wahyudi, Tauficky Hidayat, Moh. Jufriyadi Sholeh, and Encung. While the secondary sources in this study are supporting data to the primary sources, both in the form of notes, literature and other supporting data. Data were collected through in-depth interviews, observations, and document analysis conducted on lecturers at Al-Amien Prenduan University. The results of this study state that Al-Amien University has implemented curriculum diversification that covers various aspects, including skills development, technology integration, and an emphasis on entrepreneurship. The curriculum implemented is designed to meet the needs of students and the demands of the job market. Although there has been progress in curriculum diversification, this study also identified several challenges, namely: Limited Resources, Resistance to Change, Stakeholder Involvement. Then the implications of curriculum diversification show the impact of providing positive impacts on students, including: Improving the Quality of Graduates, Student Self-Awareness, Readiness for Entrepreneurship